R-spondin 1 protects against inflammatory bone damage during murine arthritis by modulating the Wnt pathway - Krönke, Gerhard; Uderhardt, Stefan; Kim, Kyung-Ah; Stock, Michael; Scholtysek, Carina; Zaiss, Mario; Surmann-Schmitt, Cordula; Luther, Julia; Katzenbeisser, Julia; David, Jean-Pierre; Abdollahi-Roodsaz, Shahla; Tran, Karolyn; et al. (Arthritis and Rheumatism, 2010)
Objective. During the course of different musculoskeletal diseases, joints are progressively damaged by inflammatory, infectious, or mechanical stressors, leading to joint destruction and disability. While effective strategies to inhibit joint inflammation, such as targeted cytokine-blocking therapy, have been developed during the last decade, the molecular mechanisms of joint damage are still poorly understood. This study was undertaken to investigate the role of the Wnt pathway modulator R-Spondin 1 (RSpo1) in protecting bone and cartilage in a mouse model of arthritis. Methods. Tumor necrosis factor α (TNFα)-transgenic mice were treated with vehicle or Rspo1. Mice were evaluated for signs of arthritis, and histologic analysis of the hind paws was performed. Moreover, we determined the effect of Rspo1 on Wnt signaling activity and osteoprotegerin (OPG) expression in murine primary osteoblasts. Results. The secreted Wnt pathway modulator RSpo1 was highly effective in preserving the structural integrity of joints in a TNFα-transgenic mouse model of arthritis by protecting bone and cartilage from inflammation-related damage. RSpo1 antagonized the Wnt inhibitor Dkk-1 and modulated Wnt signaling in mouse mesenchymal cells. In osteoblasts, RSpo1 induced differentiation and expression of OPG, thereby inhibiting osteoclastogenesis in vitro. In vivo, RSpo1 promoted osteoblast differentiation and bone formation while blocking osteoclast development, thereby contributing to the integrity of joints during inflammatory arthritis. Conclusion. Our results demonstrate the therapeutic potential of RSpo1 as an anabolic agent for the preservation of joint architecture. © 2010, American College of Rheumatology.
CRIS-Team Scopus Importer:2020-11-20